Cancer-Related Venous Thromboembolism: From Pathogenesis to Risk Assessment - Costa, José; Araújo, António (Seminars in Thrombosis and Hemostasis, 2021)
Cancer-related venous thromboembolism (VTE) remains a major health problem, accounting for at least 18% of all cases of VTE. Cancer patients with VTE have worse prognosis than those without VTE. Prophylaxis reduces VTE risk, but it is not feasible for all outpatients with cancer due to an increased bleeding risk. The factors involved in the pathogenesis of cancer-related VTE are direct coagulation activation, platelet activation, induction of inflammatory responses, and inhibition of fibrinolysis. Direct coagulation activation can be due to cancer procoagulant (a cysteine protease), microvesicles, or other prothrombotic abnormalities. Risk factors for developing VTE in cancer patients can be divided into four groups: tumor-related risk factors, patient-related risk factors, treatment-related risk factors, and biomarkers. Cancers of the pancreas, kidney, ovary, lung, and stomach have the highest rates of VTE. Patient-related risk factors such as age, obesity, or the presence of medical comorbidities can contribute to VTE. Platinum-based chemotherapies and antiangiogenesis treatments have also been associated with VTE. Biomarkers identified as risk factors include high platelet count, high leukocyte count, P-selectin, prothrombin fragments, D-dimer, and C-reactive protein. Based on the known risk factors, risk assessment models were developed to stratify patients who would benefit from thromboprophylaxis. The Khorana model was the first and is still the most widely used model. Because of its low sensitivity for certain tumor types, four new models have been developed in recent years. In this review, we describe the current knowledge about the pathogenesis and risk factors for cancer-related VTE, hoping to contribute to further research on the still many obscure aspects of this topic.
Keywords: cancer; venous thromboembolism; risk assessment; biomarkers; cancer procoagulant